Contemporary Manifestations of Islamic Arts in the UAE, Meaning and Representation - Mohamed El Amrousi (Journal of Architecture, Planning and Construction Management, 2020)
The Emirates Palace hotel in Abu Dhabi triggered much debate due to its revival of clearly referenced forms to the Mughal Dynasty in Islamic India, thereby by passing local building traditions. The over whelming display of diverse arts and crafts of Islam compressed in time and space, stand in contrast to Qasr al-Sarab with its clear reference to local heritage such as Al-Jahili Fort in Al-Ain. In both cases they represent a form reconstructed heritage with clear lineages Arab/Islamic architecture without attempts of reinterpretation or abstraction. These hotel/resorts and the architectural manifestations they emanate are intrinsic parts of a trend in Abu Dhabi to search for an architectural identity in a rapidly growing modern Arab city. In both cases motifs of an Arab/Muslim referendum have been imported from a spectrum of Islamic arts and crafts, to be displayed in situ, as subjects with conscious semiotics to dynastic Arab/Muslim pasts. This study addresses representations of contemporary Islamic forms emerging in the UAE and juxtaposes Qasr al-Sarab with its integration of desert/adobe forms to the Emirates Palace with its display and acquisition of arts of the Muslim world. In many ways both hotel/resorts replace the museum as an institution that is not yet fully developed in Abu Dhabi, and thereby are part of a strategy to create a collective memory for the city as the capital of an emerging modern Arab Nation State.